Guava Leaf Meal (Psidium guajava L.) in Broiler Diets: Effects on Performance, Nutrient digestibilty, and Intestinal Morphology - Blandon Martínez, Juan Carlos; Vásquez David, Luz Estella; Castaño Peláez, Hader Iván; Londoño Franco, Luis Fernando; Soto Londoño, Camilo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
This study investigated the effect of guava leaf meal (GLM) as a phytobiotic in broilers, focusing on its chemical properties and potential physiological benefits. 135 one-day-old male Cobb broilers were randomly allocated to five treatments (nine replicates per treatment and three birds per replicate): a basal diet with regulated commercial antibiotic (T1), without regulated commercial antibiotic or growth promoters (T2), 1% GLM (T3), 1.5% GLM (T4), and 2% GLM (T5) for 38 d. T2, T3, T4, and T5 reduced feed intake (FI) during the finishing phase (days 20–38, P < 0.0001), but there were no statistical differences in accumulated feed intake (AFI) between treatments. GLM groups had lower ADG during the starter phase (days 3-20, P < 0.05), but there were no statistical differences in accumulated gain. Accumulated feed conversión rate (FCR) was better in T2 to T5 compared to T1 (P < 0.05). GLM groups (T3, T4 and T5) showed significantly higher values of nutrient digestibility (P < 0.05). Duodenum morphology showed that number of villi (P=0.02) and the villus height (P= 0.03) increased with GLM supplementation with respect to control groups (T1 and T2). In conclusion, GLM-based diets enhanced nutrient digestibility and improved intestinal architecture, thereby supporting their inclusion in broiler chicken diets to optimize production efficiency. Highlights: Dietary inclusion of 1.5-2% Guava Leaf Meal significantly enhanced apparent nutrient digestibility in broiler chickens, particularly crude protein and phosphorus. GLM supplementation improved duodenal morphology by increasing villus height and villus number, suggesting enhanced nutrient absorption capacity. Although feed intake was reduced during the finisher phase, overall feed conversion ratio (FCR) was significantly improved with GLM, indicating better feed efficiency. Guava Leaf Meal demonstrated potential as a natural phytobiotic alternative to conventional antibiotics for optimizing broiler production performance and intestinal health.